2004
DOI: 10.1186/bcr975
|View full text |Cite
|
Sign up to set email alerts
|

Knockdown of c-Myc expression by RNAi inhibits MCF-7 breast tumor cells growth in vitro and in vivo

Abstract: Introduction Breast cancer is the leading cause of cancer death in women worldwide. Elevated expression of c-Myc is a frequent genetic abnormality seen in this malignancy. For a better understanding of its role in maintaining the malignant phenotype, we used RNA interference (RNAi) directed against c-Myc in our study. RNAi provides a new, reliable method to investigate gene function and has the potential for gene therapy. The aim of the study was to examine the anti-tumor effects elicited by a decrease in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
50
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 136 publications
(52 citation statements)
references
References 37 publications
2
50
0
Order By: Relevance
“…Additionally, Sp1 can directly interact with the c-Jun transcription factor to modulate the up-regulation of vimentin, a protein commonly found misregulated in metastatic tumors (40). Sp1 itself has been shown to be a useful molecular marker is gastric cancer and Sp1 expression has been shown to be closely associated with patient survival rate (16,41).…”
mentioning
confidence: 99%
“…Additionally, Sp1 can directly interact with the c-Jun transcription factor to modulate the up-regulation of vimentin, a protein commonly found misregulated in metastatic tumors (40). Sp1 itself has been shown to be a useful molecular marker is gastric cancer and Sp1 expression has been shown to be closely associated with patient survival rate (16,41).…”
mentioning
confidence: 99%
“…Another study showed that siRNA could be used in vitro to inhibit West Nile virus replication. It was also found that siRNAs could provide some protection from lethal West Nile virus infection in mice [67]. Recently, potent siRNA inhibitors of SARS coronavirus in vitro have been shown to highly effective in suppressing SARS-like symptoms and phenotypes in an in vivo rhesus macaque SARS model using clinical viable delivery methods [69].…”
Section: Therapeutic Applicationsmentioning
confidence: 98%
“…In one study, researchers found that the growth of the human breast cancer derived cell line MCF-7 could be inhibited by siRNA targeted to the c-myc gene in vitro and in vivo [67]. In another study it was found that siRNA could be used to decrease the expression of IL-10 on both the mRNA and protein levels in a dose and time dependant manner [58].…”
Section: Therapeutic Applicationsmentioning
confidence: 99%
See 2 more Smart Citations